Dynamic Parallelism in GPU Optimized Barnes Hut Trees for Molecular Dynamics Simulations - Carranza, Melisa (Wake Forest University, 2017)
Since the beginning of the modern computing era, high performance computing has been pushing the boundaries of the types of problems that can be solved in many different disciplines. One of the leading fields is computational biophysics where molecular dynamics (MD) simulations provide microscopic resolution details of how biomolecules move, fold, and assemble into intricate complexes that perform biological functions. However, it still remains a challenge to accurately perform MD simulations of biologically relevant complexes at timescales that can be directly compared with experiments. While the fundamental features of biomolecular dynamics, folding, and assembly are very interesting, their misfolding or misassembly can lead to deleterious repercussions that lead to diseases such as Parkinson's and Alzheimer's. MD simulations have played key roles in successes so far in directing experiments that lead to therapies, but advances in high performance computing hardware and algorithms will expand the scope of the problems that can be solved.
Keywords: barnes hut trees; coarse grained simulations; cuda; dynamic parallelism; high performance computing; molecular dynamics